Identification of an Acinetobacter pittii acyltransferase involved in transformation of deoxynivalenol to 3-acetyl-deoxynivalenol by transcriptomic analysis - Yuxuan Liu; Laipeng Xu; Ziyao Shi; Ruolin Wang; Yang Liu; Yujie Gong; Yadong Tian; Xiangtao Kang; Xiangli Sun; Yanbin Wang (Ecotoxicology and Environmental Safety, 2023)
Deoxynivalenol (DON), a mycotoxin primarily produced by Fusarium graminearum (F. graminearum), is widely present in food and feed, posing great hazards to human and livestock health. In this study, a strain of Acinetobacter pittii (A. pittii) S12 capable of degrading DON was isolated from soil samples and identified through morphological characterization, biochemistry analysis, and 16 S rRNA gene sequencing. The results of HPLC-MS indicated that the degradation products underwent a conversion from [M-H]- to [M+CH3CO], with concomitant transformation of the hydroxyl group into an acetyl moiety. Based on transcriptome sequencing analysis, the acyltransferase encoded by DLK06_RS13370 was predicted to be the pivotal gene responsible for DON biotransformation. The result of molecular docking analysis suggest a high affinity between the enzyme and DON. The recombinant protein encoded by DLK06_RS13370 was expressed in Escherichia coli (E. coli) and demonstrated the capacity to catalyze the conversion of DON into 3-Acetyl-deoxynivalenol (3-ADON), as confirmed by HPLC analysis. In conclusion, our findings confirm that the acyltransferase encoded by DLK06-RS13370 is responsible for the acetylation of DON. This sheds light on the co-occurrence of DON and its acetyl-derivatives in wheat-based products. Data Availability: Not applicable.